UPAYA PENGENALAN HURUF HIJAIYAH MELALUI PERMAINAN PAPAN ROLET HURUF HIJAIYAH DI RAUDHATUL ATHFAL SALIMPAT - Wernita, Musni Firda (Jurnal Ilmiah Pesona PAUD, 2012)
The fact that the researchers saw that letter recognition in preschool children hijaiyah RA Salimpat still low on hijaiyah letters. This is because the lack of instructional media to enhance literacy hijaiyah children. This study aimed to determine whether through board games roulette hijaiyah letters, letter recognition skills in kindergarten children hijaiyah RA Salimpat B1 group could increase.This type of research is action research class conducted two cycles of the cycle I and cycle II.